Company law - Dignam, Alan; Lowry, John (Oxford : Oxford University Press, 2012)
Company law is a popular company law textbook, providing an accessible writing style demystifying complex areas of law without over-simplification. This book focuses on key principles taught on undergraduate courses and explores corporate theory in some depth
1. Fundamental principles -- 2. Behind the corporate veil -- 3. Issues of corporate authority
Previous ed.: 2010
Includes bibliographical references and index
Keywords: Corporation law -- England; Corporation law -- Wales